Multi-Vector Energy Markets for Resilient Grid-Connected Renewable Networks - R. Rajasree; D. Lakshm; K. Stalin; R.Karthick Manoj (CV Media Inti Teknologi, 2025)
Background of Study: The transition to renewable energy is becoming more complex with the emergence of multi-vector energy systems that integrate electricity, heat, gas, and transportation networks. Managing these interconnected systems requires advanced market mechanisms that can handle the variability of renewable sources while ensuring efficient and reliable energy distribution. Aims and Scope of Paper: This paper evaluates current renewable energy market protocols and proposes a hybrid model to improve grid reliability, flexibility, and efficiency using optimization and game theory. Methods: The study used optimization and game theory to model energy trading, developed a hybrid market with storage and demand response, and assessed dynamic pricing’s impact on load shifting and prosumer behavior. Result: Simulation outcomes showed that dynamic pricing schemes encourage prosumers to shift loads, leading to higher energy efficiency, reduced supply restrictions, and improved grid stability. The model also improved cost-effective resource management across interconnected energy systems. Conclusion: The study shows that a multi-vector hybrid energy market enhances resilience, flexibility, and sustainability, offering key guidance for energy policy development.